Studies on gene control regions. VI. The 5- methyl of thymine, a lac repressor recognition site. - Goeddel, D V (1977)
Three site specific deoxyuridine analogs of lac operator were tested for binding with wild type (SQ) and tight binding (QX86) lac repressors. Insertion of uracil for thymine at site 13 (our nomenclature) significantly reduced the dissociation half-life of QX86 repressor for lac operator DNA (21 vs 1.2 min). Two other sites (6 and 7) are affected to a much lesser extent.